When does a healthy lifestyle turn into a disorder? Orthorexia - diagnostic problems, methods of treatment - Karolina Zalewa; Wojciech Kapłan; Dominika Rachwał; Lidia Bartoszek; Joanna Olszak; Monika Rogowska; Rafał Świdziński; Jakub Lipiec; Bartosz Skorupski; Ewa Piątek (Kazimierz Wielki University, 2023)
Introduction: Orthorexia nervosa (ON) is a common phenomenon. Its prevalence in society ranges from 1% to 60%. Yet, there are no specific diagnostic criteria or effective screening tests. Moreover, orthorexia does not appear in any of the available international psychiatric classifications such as the ICD (International Statistical Classification of Diseases and Related Health Problems) and DSM (Diagnostic and Statistical Manual of Mental Disorders). Due to this fact many people remain undiagnosed, which significantly affects their standard of living, and later puts a strain on the health care system. Material and method: The article is based on a study and analysis of available publications in the last few years, published in the PubMed database. Conclusions: It is crucial to create specific diagnostic criteria for orthorexia. This will enable efficient detection of patients at an early stage of the disorder, which will significantly shorten the diagnostic path. Moreover, specifying potential risk factors will help to reduce new cases.